ANALYSIS OF COMPETITIVE ADVANTAGE IN IMPROVING THE QUALITY OF INDONESIAN MSME PRODUCTS TO FACE THE DOMINATION OF CHINESE IMPORTED PRODUCTS IN THE ASEAN CHINA FREE TRADE AREA (ACFTA). - Rufida Tahta (UNIDA GONTOR, 2021)
This study discusses Indonesia's strategy in helping MSMEs face the dominance of imported Chinese products in the Indonesian domestic market. Since the enactment of the ACFTA agreement, MSMEs, which are an important pillar of the Indonesian economy, have felt a significant negative impact. This is due to globalization that has changed the order in various aspects of life, especially the world economy, where countries are required to carry out free trade which includes the application of a 0 tariff policy in import exports. Due to Indonesia's lack of readiness in facing the free trade era, this caused MSMEs and domestic industries to go out of business because they were unable to compete with various imported goods originating from China. The purpose of this study is to analyze how the Indonesian government supports MSMEs in facing the dominance of imported Chinese products in Indonesia after the ACFTA cooperation. In this study, researchers discussed the increase in MSMEs in terms of product quality and quantity and the increase in human resources, which has never existed in previous research in accordance with the title that the researchers took, namely